2257: Vaccine efficacy and immunogenicity of recombinant WAP and CAP-1 proteins in AKR mice. Issue 1 (10th May 2018) - Briggs, Neima; Versteeg, Leroy; Zhan, Bin; Mejia, Rojelio; Keegan, Brian; Beaumier, Coreen; Sastry, Jagannadha; Elena Bottazzi, Maria; Hotez, Peter
Abstract : OBJECTIVES/SPECIFIC AIMS: Trichuris trichiura, is a leading cause of chronic colitis worldwide, resulting in growth stunting, anemia, and cognitive deficits, predominately in children. Our long-term goal is to develop a vaccine against T. trichiura . Both T. trichiura and the closely related Trichuris muris release excretory/secretory (ES) macromolecules from the stichosome organ, which facilitates intracellular invasion into the cecum. We exploited the high degree of genetic sequence homology between T. trichiura and T. muris to evaluate T. muris stichosome proteins as vaccine candidates. METHODS/STUDY POPULATION: Through immunological screening of the T. muris stichosome cDNA library and T. muris ES macromolecules generated in culture, we identified, cloned, and expressed several vaccine candidates. In ranking these antigens, we selected the most promising recombinant proteins, WAP and CAP-1, and vaccinated AKR mice to evaluate the immunogenicity and efficacy of our candidate. In addition, we collected 240 serum samples in the T. trichiura endemic region of Honduras to measure the recognition of WAP and CAP-1 in naturally infected human. RESULTS/ANTICIPATED RESULTS: We measured a statistically significant reduction in larval worm burden in WAP and ES vaccinated mice, but not CAP-1, by microscopy and real-time PCR of T. muris DNA. We found a significant relationship between antigen-specific IgG1:IgG2a ratio in the mouse serum and degree of protection. Mouse splenocytes, vaccine-sensitized draining lymph nodes, and mesenteric lymph nodes were antigen-stimulated and their secreted Th1, Th2, and Th17 cytokines were measured by Luminex ® . Stimulated mouse lymphoid cells were further analysed for T helper, T cytotoxic, and central/effector memory T cells by Flow Cytometry. Human IgG1, IgG2, and IgE antibody titers against WAP and CAP-1 were measured by ELISA. DISCUSSION/SIGNIFICANCE OF IMPACT: In our study, we describe the T cell dependent mechanism of humoral immunity of 2 promising ES-derived vaccines recombinant proteins, WAP and CAP-1. We evaluated the immune response, indicating a driving a Th2-induced humoral response necessary for protection. We further predict protection and allergenicity of WAP in humans using serum from a cohort in an T. trichiura endemic region.